Reduction of refractory Maillard reaction products by Fe³⁺ during thermal hydrolysis pretreatment and enhanced sludge biodegradability - Geng, Yikun (2022)
Refractory Maillard reaction products (MRPs) produced during thermal hydrolysis pretreatment (THP) of waste activated sludge (WAS) may negatively impact the performance of downstream anaerobic digestion (AD) and nitrogen removal processes. Operating THP at lower temperature can mitigate the production of MRPs and improve biodegradability of WAS, while solubilization of WAS is reduced. This study intends to develop a method to reduce the refractory MRPs of WAS without compromising on the solubilization. Fe3+ was introduced into THP process (165 °C, 30 min) to mitigate Maillard reaction. Effects of Fe3+ on solubilization of WAS, reduction of refractory residuals, accumulative methane production, and microbial community shift were studied. Results confirm that solubilization of WAS was improved and refractory residuals were reduced with the amendment of 10 mg-Fe/L FeCl3. MRPs mitigation mechanisms were investigated and mainly attributed to Fe3+-triggered Fenton-like reactions. Methane production was enhanced by 10.4 ± 0.8% and attributed to the improved biodegradability of THP liquor, as well as to the enrichment of protein degradation and methane production related microbial community. This work provides a simple, economical, and safe strategy to reduce refractory residuals discharged from THP-AD system and to enhance methane production for more energy recovery.